Two-dimensional MXenes: recent emerging applications. Issue 39 (5th September 2022) - Goel, Neeraj; Kushwaha, Aditya; Kumar, Mahesh
Abstract : This review analytically summarises the state-of-art advances of MXene based devices with a particular emphasis on modern applications. Abstract : MXenes, are a rapidly growing family of two-dimensional materials exhibiting outstanding electronic, optical, mechanical, and thermal properties with versatile transition metal and surface chemistries. A wide range of transition metals and surface termination groups facilitate the properties of MXenes to be easily tuneable. Due to the physically strong and environmentally stable nature of MXenes, they have already had a strong presence in different fields, for instance energy storage, electrocatalysis, water purification, and chemical sensing. Some of the newly discovered applications of MXenes showed very promising results, however, they have not been covered in any review article. Therefore, in this review we comprehensively review the recent advancements of MXenes in various potential fields including energy conversion and storage, wearable flexible electronic devices, chemical detection, and biomedical engineering. We have also presented some of the most exciting prospects by combining MXenes with other materials and forming mixed dimensional high performance heterostructures based novel electronic devices.